If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9s + 2t + -4s = 0 Reorder the terms: 9s + -4s + 2t = 0 Combine like terms: 9s + -4s = 5s 5s + 2t = 0 Solving 5s + 2t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2t' to each side of the equation. 5s + 2t + -2t = 0 + -2t Combine like terms: 2t + -2t = 0 5s + 0 = 0 + -2t 5s = 0 + -2t Remove the zero: 5s = -2t Divide each side by '5'. s = -0.4t Simplifying s = -0.4t
| In(5*x^2)=3+In(a) | | -5=-3x-17 | | f(x)=x^2+4x+17 | | X=13+(7x-13) | | 24x-7-13x+4=25x-8-14x+16 | | v/9.8=23 | | 2(10t)=30+10 | | W=1/6v | | -5=2x-23 | | 4/(-1)=n | | 10x-6=10x-20 | | 5(x-20)=190 | | m/π=7.3 | | x-2=-6x-18 | | 5.8m=.5 | | 5(x-10)-3=6x-46 | | 2-1+4+4-3= | | x-2=6x+18 | | 1/2x-3/4=3/8 | | (5+x)-6=7 | | 2(10*2)=30+10 | | 3x-44=56-2x | | x/12-15=36 | | -3n=-5 | | 40=3/4x-32 | | 2(10*10)=30+10 | | 21-3=18 | | 21x+7=3x+1621-3 | | 2x/8-3/4=5/12 | | 5+8m=7m+2 | | -9a-3=-36 | | 5-8x=16-8 |